Bacillus paralicheniformis LN33 fermented feed improves growth performance in Cherry Valley ducks by enhancing immune function and intestinal barrier integrity - Jiang, Yilong; Yang, Xiaofei; Lei, Yi; Li, Songlin; Chen, Xianxin; Jiang, Li (Frontiers in Veterinary Science, 2025)
IntroductionThis study investigated the effects of feed fermented with Bacillus paralicheniformis LN33 on growth performance, antioxidant capacity, immune response, intestinal barrier function, and gut microbiota in Cherry Valley ducks.MethodsA total of 480 healthy 7-day-old Cherry Valley ducks (197.33 ± 5.90 g) were randomly divided into four groups. One group received a basal diet (control), while the other three received the basal diet supplemented with 1%, 3%, or 5% fermented feed for 28 days.ResultsDucks fed 3% fermented feed showed significantly higher final body weight (3,020.00 ± 52.20 g) and average daily gain (100.79 ± 1.73 g) than the control group (2,896.00 ± 120.93 g and 96.39 ± 4.23 g, respectively; P < 0.05). The feed-to-gain ratio decreased significantly (1.79 ± 0.03 vs. 1.87 ± 0.08; P < 0.05), with similar feed intake across groups. Antioxidant enzyme activity increased, while pro-inflammatory cytokine levels decreased. Expression of intestinal tight junction proteins and immune markers improved. The relative abundances of Faecalibacterium, Odoribacter, and Butyricicoccus increased significantly and were positively correlated with intestinal and immune function.DiscussionThese results suggest that B. paralicheniformis-fermented feed enhances growth performance and overall health in Cherry Valley ducks by boosting antioxidant defenses, modulating immune responses, and reshaping the gut microbiota.